Loss of the Protein Cystathionine β-Synthase During Kidney Injury Promotes Renal Tubulointerstitial Fibrosis - Xiangning Yuan; Jin Zhang; Feifei Xie; Wenqing Tan; Shuting Wang; Ling Huang; Lijian Tao; Qiqi Xing; Qiongjing Yuan (Karger Publishers, 2017)
Background/Aims: Renal tubulointerstitial fibrosis (TIF) is the common pathway of progressive chronic kidney disease. Inflammation has been widely accepted as the major driving force of TIF. Cystathionine β-synthase (CBS) is the first and rate-limiting enzyme in the transsulfuration pathway. CBS is considered to play protective role in liver and pulmonary fibrosis, but its role in TIF remains unknown. The purpose of this study was to investigate the potential role and mechanism of CBS in renal inflammation and TIF. Methods: Renal function, tubulointerstitium damage index score, extracellular matrix (ECM) deposition, and the expressions of collagen I, collagen III, fibronectin, CD3, CD68, IL-1β, TNF-α were measured in sham operation and unilateral ureteral obstruction (UUO) rats. Proteomics and gene array analysis were performed to screen differentially expressed molecules in the development of renal inflammation and TIF in UUO rats. The expression of CBS was detected in patients with obstructive nephropathy and UUO rats. We confirmed the expression of CBS using western blot and real-time PCR in HK-2 cells. Overexpression plasmid and siRNA were transfected specifically to study the possible function of CBS in HK-2 cells. Results: Abundant expression of CBS, localized in renal tubular epithelial cells, was revealed in human and rat renal tissue, which correlated negatively with the progression of fibrotic disease. Expression of CBS was dramatically decreased in the obstructed kidney from UUO rats as compared with the sham group (SHM). In addition, knocking down CBS exacerbated extracellular matrix (ECM) deposition, whereas CBS overexpression attenuated TGF-β1-induced ECM deposition in vitro. Inflammatory and chemotactic factors were also increased in CBS knockdown HK-2 cells stimulated by IL-1β. Conclusions: These findings establish CBS as a novel inhibitor in renal fibrosis and as a new therapeutic target in patients with chronic kidney disease.